Penguatan Aspek Legalitas dalam Pembentukan Koperasi Syariah di Desa Rancatungku - Sugiartiningsih Sugiartiningsih; Iman Harjono; Erfan Erfiansyah; Toto Sugihyanto; Siti Kodariah; Hanifah Nurhalimah; Yasar Muhammad Farhan (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2025)
Cooperatives, as dynamic organizations that meet the needs of members, must be legally incorporated in order to be eligible to do business and be able to increase Indonesia's economic competitiveness. Rancatungku is a developing village that has high potential in establishing sharia cooperatives, including BMT Al-Jamaah in Kampung Mengger RW 01. The purpose of PkM is to socialize the formation of cooperatives in terms of form and type according to the Job Creation Law. The PkM implementation method is a lecture based on the questions asked, followed by a question and answer session with PkM participants who are representatives of the management and members of BMT Al-Jamaah. The results of the activity showed that partners were able to respond to the knowledge provided by the speakers regarding the definition, reasons for cooperatives, types, forms, and expectations of cooperatives, as evidenced by the increase in understanding scores. In the discussion, participants were also able to describe their experiences during cooperatives, including deviant member behavior, such as the motivation to join cooperatives only to borrow. The speakers responded through a religious approach and emphasized the importance of following government regulations, especially in terms of the legality of cooperatives. Keywords: cooperatives, legality, sharia, regulation, government